Lineage-specific evolution of Methylthioalkylmalate synthases (MAMs) involved in glucosinolates biosynthesis - Zhang, Jifang; Wang, Xiaobo; Cheng, Feng; Wu, Jian; Liang, Jianli; Yang, Wencai; Wang, Xiaowu (Frontiers in Plant Science, 2015)
Methylthioalkylmalate synthases (MAMs) encoded by MAM genes are central to the diversiﬁcation of the glucosinolates, which are important secondary metabolites in Brassicaceae species. However, the evolutionary pathway of MAM genes is poorly understood. We analyzed the phylogenetic and synteny relationships of MAM genes from 13 sequenced Brassicaceae species. Based on these analyses, we propose that the syntenic loci of MAM genes, which underwent frequent tandem duplications, divided into two independent lineage-specific evolution routes and were driven by positive selection after the divergence from Aethionema arabicum. In the lineage I species Capsella rubella, Camelina sativa, Arabidopsis lyrata, and A. thaliana, the MAM loci evolved three tandem genes encoding enzymes responsible for the biosynthesis of aliphatic glucosinolates with different carbon chain-lengths. In lineage II species, the MAM loci encode enzymes responsible for the biosynthesis of short-chain aliphatic glucosinolates. Our proposed model of the evolutionary pathway of MAM genes will be useful for understanding the specific function of these genes in Brassicaceae species.